Plaque Reduction Technique for Demonstrating Neutralizing Antibodies for Chlamydia - Banks, J. (1970)
Some members of the genus Chlamydia (Bedsonia or psittacosis-lymphogranuloma venereum-trachoma-inclusion conjunctivitis group of microorganisms) produce plaques in monolayers of mouse fibroblast (L-929) cells. Hyperimmune chicken antisera may be capable of specifically reducing plaque counts. When the test was applied to chlamydiae isolated from avian species, the results indicated that different isolates with a common source had similar antigenic reactivity. The plaque reduction test is a potentially useful method for serotyping chlamydiae. The difficult aspect of the method appears to be a readily reproducible means of producing neutralizing antiserum.